The Effect of Implementing Conceptual Understanding Procedures (CUPs) with Handouts on Learning Outcomes in Physics at SMPN 3 Sikakap - Sakulo, Maria Elisabeth; Rahmi, Aidhia; Anaperta, Megasyani (COMPTON: Jurnal Ilmiah Pendidikan Fisika, 2023)
This study is motivated by the fact that students' physics learning outcomes have not met the Minimum Completion Criteria (KKM). The aim of this research is to determine the effect of applying the Conceptual Understanding Procedures (CUPs) learning model on students' physics learning outcomes. This study uses a quasi-experimental design. The population consists of all Grade VIII students, which includes two classes. Sampling was conducted using saturated sampling. Data analysis techniques were applied to both cognitive and affective domains to test hypotheses with homogeneous and variance conditions. The t-test results show that there is an effect on students' physics learning outcomes using the Conceptual Understanding Procedures (CUPs) learning model.